A STUDY OF THE CONCEPT OF HETEROTOPIAN SPACE IN THE DUTCH CEMETERY AT THE BOGOR BOTANICAL GARDEN - Kurniawan, Nur Muhammad Arief; Marwoto, Irmawati (UI Scholars Hub, 2023)
A cemetery is a land that is used as a place for burial of bodies. However, despite its obvious function, in European Christian culture which lasted for centuries, the view of the true cemetery was always changing, so that the function of the cemetery was often mixed with other completely unrelated functions of space. This phenomenon is highlighted by Foucault in his theory of heterotopia space (1967). In this regard, this study intends to look at other spaces based on the phenomena found in the Dutch Cemetery at the Bogor Botanical Garden. This cemetery is interesting to study using Foucault's heterotopia theory because of its relatively different location from the Dutch cemeteries in the Dutch East Indies at that time, which were generally located in a church environment or in an open field. Based on the results of the study, it is concluded that in the Bogor Botanical Garden cemetery, there are other spaces which are manifested in three heterotopological principles, namely: the concept of heterotopia space of crisis and deviation, changes in the function of the cemetery, and the incorporation of other unrelated spaces.